Return to Sport After ACL Reconstruction: Strength and Functionality Testing - Simon J. Padanilam BA; Steven R. Dayton BA; Ryan Jarema PT, ATC; Michael J. Boctor BA; Vehniah K. Tjong MD (SAGE Publishing, 2021)
Background: Functionality testing following anterior cruciate ligament (ACL) reconstruction can benefit clinicians and patients in determining readiness for return to sport. While a component of a multifactorial decision, inability to perform well on these tests predicts increased risk of reinjury. As of 2013, only 41% of orthopaedic surgeons report using strength or functionality testing in evaluating patients for return to sport (RTS). Indications: In the intermediate to late stages of their rehabilitation program, patients may undergo these tests to determine readiness and safety to return to sport. Technique Description: The tests described in this video include the single and triple hop for distance, triple crossover hop, single and double vertical leg jump tasks, drop jump landing task, and isokinetic and isometric strength testing. Results: Clinicians who incorporate these tests into patient rehabilitation programs may reduce patient risk of ACL reinjury by 75% to 84%. The limb symmetry index (LSI) is a reliable calculated measure for these tests, with a strong reliability for the hop tests. The limb symmetry index can be calculated for each test and represents the ratio of measured performance of the involved, or post-ACL reconstruction, leg when compared against the uninvolved leg. The commonly used limb symmetry index threshold for passing each hop test is 90%. Patients who score 90% or greater on each of these tests are less likely to experience knee reinjury. Discussion/Conclusion: The ability of knee strength and functionality tests in determining RTS following ACL reconstruction has been highlighted as a tool in potentially reducing risk of knee reinjury. Other isometric and isokinetic testing can be used in addition to the described functionality tests but may not be possible in certain practices due to equipment and funding limitations. Usage of these strength and functionality tests, in conjunction with clinician evaluation, may lead to more optimal outcomes for patients and lower rates of reinjury. Psychological assessment may aid in evaluating patient readiness for return to sport. Importantly, further sport-specific testing is still recommended and will optimize patient outcomes.